Frame your Leadership - Rebecca L Koltz; Melissa Odegard (Academic Chairpersons Conference Proceedings, 2023)
Participants will engage with Bolman and Deal’s four frames of leadership model to gain insight and look at issues facing their departments from multiple perspectives. Come to this presentation and learn what frame(s) you use most and understand how to interact with others on your team by using different frames.
Keywords: leadership frames; insight; perspectives; model